2022
DOI: 10.3389/fpubh.2022.1015425
|View full text |Cite
|
Sign up to set email alerts
|

Association between food insecurity and kidney stones in the United States: Analysis of the National Health and Nutrition Examination Survey 2007–2014

Abstract: PurposeAlthough food insecurity is a major public health concern associated with various diseases, the relationship between food insecurity and kidney stones remains unclear. We aimed to investigate the association between food insecurity and kidney stones in the US population.Materials and methodsFour continuous cycles of data from the year 2007 to 2014 were obtained from National Health and Nutrition Examination Survey (NHANES) in the current study. We utilized the Household Food Security Module to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…This was ascertained by the participant’s response to the question, “Have you/Has sample person (SP) ever had a kidney stone?” Those who answered ‘yes’ were categorized as having nephrolithiasis. The validity of self-reported data on the occurrence of kidney stones has been confirmed by previous studies ( 4 , 23 , 24 ).…”
Section: Methodssupporting
confidence: 73%
See 1 more Smart Citation
“…This was ascertained by the participant’s response to the question, “Have you/Has sample person (SP) ever had a kidney stone?” Those who answered ‘yes’ were categorized as having nephrolithiasis. The validity of self-reported data on the occurrence of kidney stones has been confirmed by previous studies ( 4 , 23 , 24 ).…”
Section: Methodssupporting
confidence: 73%
“…Those who answered 'yes' were categorized as having nephrolithiasis. The validity of selfreported data on the occurrence of kidney stones has been confirmed by previous studies (4,23,24).…”
Section: Exposure Variables and Outcomessupporting
confidence: 65%
“…A previous study showed that there existed a significant association between food insecurity and kidney stones. 35 In addition, it was now generally accepted that kidney stone was also associated with metabolic abnormalities in the body, such as hyperparathyroidism and hypercortisolism. 36 Both thyroid function and cortisol function were regulated by the brain and nerves, and studies have shown that nutritional deficiencies have a direct and severe impact on brain and nerve development.…”
Section: Discussionmentioning
confidence: 99%
“…The NHANES is a population-based cross-sectional survey designed to assess health and nutritional status within the US population ( 14 ). Since 1999, approximately 5,000 nationally representative individuals have been surveyed annually, and related data have been published biennially.…”
Section: Methodsmentioning
confidence: 99%
“…The NHANES is a population-based cross-sectional survey designed to assess health and nutritional status within the US population (14). Since 1999, approximately 5,000 nationally In terms of smoking status, 34,657 participants out of 59,842 participants were screened in our study population.…”
Section: The Study Population In Nhanesmentioning
confidence: 99%